2014
DOI: 10.3835/plantgenome2013.11.0037
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping of Agronomic QTLs in U.S. Spring Barley Breeding Germplasm

Abstract: The use of genome-wide association studies (GWAS) to detect quantitative trait loci (QTL) controlling complex traits has become a popular approach for studying key traits in crop plants. The goal of this study was to identify the genomic regions of barley (Hordeum vulgare L.) that impact five agronomic and one quality trait in U.S. elite barley breeding lines, as well as to identify markers tightly linked with these loci for further use in barley improvement. Advanced recombinant inbred lines submitted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 73 publications
3
69
2
2
Order By: Relevance
“…Marker genotypes were imputed using the expectation maximization algorithm implemented in the rrBLUP package in R (Endelman, 2011). This marker set and genetic map (Muñoz-Amatriaín et al, 2011) have been used in studies of genomewide selection, association mapping, and population genetics of North American barley germplasm (Lorenz et al, 2012;Pauli et al, 2014;Poets et al, 2016). To infer genetic map positions, we first obtained physical and genetic map information on 3072 array-based SNPs developed during the Barley Coordinated Agricultural Project (BCAP) (Close et al, 2009).…”
Section: Training Populationmentioning
confidence: 99%
“…Marker genotypes were imputed using the expectation maximization algorithm implemented in the rrBLUP package in R (Endelman, 2011). This marker set and genetic map (Muñoz-Amatriaín et al, 2011) have been used in studies of genomewide selection, association mapping, and population genetics of North American barley germplasm (Lorenz et al, 2012;Pauli et al, 2014;Poets et al, 2016). To infer genetic map positions, we first obtained physical and genetic map information on 3072 array-based SNPs developed during the Barley Coordinated Agricultural Project (BCAP) (Close et al, 2009).…”
Section: Training Populationmentioning
confidence: 99%
“…Fusarium head blight (FHB), caused primarily by Fusarium graminearum Schwabe, is one of the most serious diseases of barley in the midwestern United States. Yield in barley, as in other crops, is a complex trait that is controlled by many loci across the genome (Hayes et al, 1993;Zhu et al, 1999;Pauli et al, 2014). Resistance to FHB and DON concentration is quantitatively inherited, and QTL associated with these traits have been identified on all barley chromosomes (de la Pena et al, 1999;Ma et al, 2000;Mesfin et al, 2003;Dahleen et al, 2003;Massman et al, 2011).…”
Section: Genomic Selection Performs Similarly To Phenotypic Selectionmentioning
confidence: 99%
“…The germplasm studied here is composed of germplasm, which was clustered according to inflorescence type, geographic origin, and breeding history. Previous studies also indicated spike morphology (two‐rowed versus six‐rowed), geographic origin, domestication or breeding history, growth habits and vernalization requirements (winter versus spring) as the major cluster factors of barley germplasm . This study also revealed a considerable level of overlap in ICARDA germplasm with NDSU lines at one end and to Ethiopian breeding lines at the other end.…”
Section: Discussionmentioning
confidence: 98%